2015
DOI: 10.1111/opo.12249
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and causes of reduced visual acuity among children aged three to six years in a metropolis in China

Abstract: The burden of reduced VA in preschool children in China was similar to that of Asian children of similar ages in the United States. Uncorrected refractive error and amblyopia were the principal causes for reduced VA among preschoolers (aged three to 6 years) in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…To our knowledge, changes in prevalence of reduced VA in preschoolers, which can reflect needs for paediatric vision care in a certain area in the past years, have not been described. In the Nanjing Pediatric Vision Project (NPVP) carried out by our research group in 2011 that enrolled 2486 children aged 48 to 60 months, we reported the prevalence of reduced PVA of 3.70% and 1.73% in the worse eye and better eye, respectively . In 2016, we conducted the comprehensive eye exam in the Nanjing Eye Study (NES) in the same age group of preschoolers of the same area using the standardized study protocol as our previous NPVP.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, changes in prevalence of reduced VA in preschoolers, which can reflect needs for paediatric vision care in a certain area in the past years, have not been described. In the Nanjing Pediatric Vision Project (NPVP) carried out by our research group in 2011 that enrolled 2486 children aged 48 to 60 months, we reported the prevalence of reduced PVA of 3.70% and 1.73% in the worse eye and better eye, respectively . In 2016, we conducted the comprehensive eye exam in the Nanjing Eye Study (NES) in the same age group of preschoolers of the same area using the standardized study protocol as our previous NPVP.…”
Section: Introductionmentioning
confidence: 99%
“…Myopia is a global public health concern associated with reduced vision and increased risks of vision‐threatening ocular complications such as retinal detachment, myopic macular degeneration, age‐related cataract and glaucoma . Myopia has generally been misconstrued to be a benign disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Any eye with presenting visual acuity < 0.3 logMAR or 6/12 with the E chart was considered to be reduced vision . The E chart was chosen as it is the most common visual acuity chart used for this age group in developing countries …”
Section: Methodsmentioning
confidence: 99%
“…If ocular disorders that hamper vision are not rectified, they can go on to impair the educational potential of the child entering school . Additionally, these disorders can affect neurodevelopment, quality of life and overall progress in childhood …”
mentioning
confidence: 99%
See 1 more Smart Citation